Application of multivariate statistical techniques in the analysis of the management of performance indicators of fixed broadband communication networks - Pedro Fernandes Neto , André; Soares da Silva, Gutembergue; Sizenando Rossiter Pinheiro, Fred; Câmara Mattozo, Teófilo; Alfredo Ferreira Costa , José (Seven Editora, 2023)
The demand for access to telecommunications services is always growing, especially those requiring broadband infrastructure, in which there is competition between networks and services platforms, contributing to leverage transformations in the economy, society and human life, resulting from numerous technological innovations that allowed the proliferation services such as internet, mobile communications and high-speed fixed and mobile connections. As a result of the great competition in this market, companies seek to find different ways to get new customers, in addition to not losing their base to competition. In the 2000s, telecommunications companies began a process of commercializing broadband internet with a product that added value to fixed telephony, the Asymmetric Digital Subscriber Line (ADLS). This study applied methods of selection of variables, through techniques of multivariate analysis of data with the purpose of evaluating the relationship of the quality of service indicators with the dropout rate (Churn).  The results obtained allow us to suggest the applicability of quality indicators in maintenance management, as well as the possibility of obtaining real economic gains for telecommunication service providers with the use of these analytical methods in their operational asset management strategies. DOI: https://doi.org/10.56238/tfisdwv1-059